A Novel Methodology to Measure the Film Thickness Profile Based on Current Stimulation for Two-Phase Flow - Sepulveda-Palma, F (IOP Publishing Ltd, 2021)
The film thickness of a two-phase flow is a parameter of interest since it is of importance to the heat and mass transfer phenomena. A novel method is proposed based on electrical impedance tomography (EIT) and conductance sensors to measure this quantity. An analytical equation is developed to relate the differential voltage associated with a current injection on the domain and the angular film thickness profile. A characteristic of the measuring procedure is that it presents a high sensitivity when the thickness is small, with the possibility of adjustment using different magnitudes of current. This model is compared experimentally and by the complete electrode model (CEM), solved by finite elements method (FEM). Results presented a good agreement with the FEM simulations, and the experimental results presented systematic error caused by the fringe effect. © 2021 IOP Publishing Ltd.